Role of single and mixed culture of Pseudomonas aeruginosa and Serratia ficaria in utilization of petroleum wastes of Dora- refineries. (Baghdad Science Journal, 2025)
The ability of single and mixed bacterial culture to utilize Dora-refineries petroleum wastes was compared. Pseudomonas aeruginosa and Serratia ficaria mixed culture consumed the wastes better than the single bacterial cultures. The highest log. number of viable cells in mixed culture was 6.842 , while in single bacterial cultures it was 6.683 and 5.631, respectively. after 3 days in API medium containing the refinery wastes. The effect of some environmental conditions on the degradation of petroleum wastes was studied included aeration , NaCl concentration , pH and temperature. The growth of bacteria in the agitated culture was higher than stagnant culture the log. of cell no. was 6.021 in the first culture. The highest log. of cell no. stagnant culture was 5.771. Pseudomonas aeruginosa AA22 and Serratia ficaria AA39 were able to grow in medium containing 5 , 7 % NaCl , they favorite pH 7. The mixed culture of the two bacteria grew well of 45 oC.